Gravity-induced phase phenomena in plate-rod colloidal mixtures - Tobias Eckert; Matthias Schmidt; Daniel de las Heras (Communications Physics, 2021)
Sedimentation experiments have shown that gravity can deeply affect bulk phenomena and sedimentation of colloidal mixtures. Here, the authors present a theoretical approach based on sedimentation paths to predict the effect of gravity on the emergence of different sedimentation phases in mixtures of anisotropic colloids.